Non Hodgkin's lymphoma of the maxilla as a first clinical manifestation of HIV infection. Report of a case. - Mokhbat, J. (1995)
Non-Hodgkin's lymphoma (NHL) of the oral cavity is rare. When it occurs, one should be suspicious of infection with the human immunodeficiency virus (HIV). NHL is the second most common malignancy associated with the acquired immunodeficiency syndrome (AIDS). This report describes the occurrence of a maxillary NHL as a primary clinical manifestation of HIV infection.